A real-world rheumatology registry and research consortium: The German RheumaDatenRhePort (RHADAR) registry - Kleinert, Stefan; Bartz-Bazzanella, Peter; von der Decken, Cay; Knitza, Johannes; Witte, Torsten; Fekete, Sándor P.; Konitzny, Matthias; Zink, Alexander; Gauler, Georg; Wurth, Patrick; Aries, Peer; Karberg, Kirsten; et al. (Journal of Medical Internet Research, 2021)
Real-world data are crucial to continuously improve the management of patients with rheumatic and musculoskeletal diseases (RMDs). The German RheumaDatenRhePort (RHADAR) registry encompasses a network of rheumatologists and researchers in Germany providing pseudonymized real-world patient data and allowing timely and continuous improvement in the care of RMD patients. The RHADAR modules allow automated anamnesis and adaptive coordination of appointments regarding individual urgency levels. Further modules focus on the collection and integration of electronic patient-reported outcomes in between consultations. The digital RHADAR modules ultimately allow a patient-centered adaptive approach to integrated medical care starting as early as possible in the disease course. Such a closed-loop system consisting of various modules along the whole patient pathway enables comprehensive and timely patient management in an unprecedented manner.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Patient-reported outcomes; Real-world data; Registry; Rheumatology; Symptom checker